STRUCTURAL CONTROL OF ALTERATION AND MINERALIZATION IN PROSPECT “X-Y”, POHUWATO REGENCY, GORONTALO PROVINCE - Wirdan, Muhammad Faisal; Rosana, Mega Fatimah; Yuningsih, Euis Tintin; Rompo, Ahmad Iryanto; Ismail, Fajar (Faculty of Geological Engineering, Universitas Padjadjaran, 2021)
The prospect “X-Y” is located in Gorontalo Province, a part of “gold district” with NW-SE arc-normal, E-W arc-parallel, and NS-NNE subsidiary lineament features and localize geological setting in the northern arm of Sulawesi. Regional geology of Sulawesi's northern arm is characterized of volcanoplutonic magmatic by typical Eocene to Recent island-arc assemblages (Hamilton, 1979). An older basement composed of granodiorite occurs in the north of the study area (Kavalieris, 1984). The study was conducted using variety of approaches, including desk top study, field mapping, and data interpretation. Desktop study are focused on lineament and fault fracture density interpretation. Field mapping include observation, measurement, and structure interpretation. Gold mineralization in the prospect “X-Y” are hosted in porphyritic dacite, lapilli tuff, and diatreme breccia unit. The type of mineralization generated epithermal low sulphidation with anomalous mineralization. It has the feature of a high fault-fracture density range of 2100-3200 m/